Cognitive impairment in victims of Russian aggression associated with post-traumatic stress disorder (PTSD) - Dolynskyi Роман; Napryeyenko Олександр (Psychosomatic Medicine and General Practice, 2024)
Abstract Among the numerous manifestations of PTSD, there are, in particular, cognitive impairments. They significantly worsen the course of PTSD and the quality of life in patients, and also reduce the probability of overcoming psychotrauma. We analyzed cognitive disorders prevalence among the civilian population of the de-occupied and affected by the full-scale Russian invasion communities of Chernihiv, Sumy, Dnipropetrovsk and Kharkiv regions. Cognitive disorders were much more common among PTSD patients (OR 4.0) and were more characteristic for women over 41 (OR 7.5 -7.7). Such PTSD sequences can lead to a substantial workability decrease, especially regarding qualified work. Thus, the analysis of the cognitive disorders prevalence in patients with PTSD lays the foundation for determining the prospects for overcoming the war consequences among the Ukrainian population.